PROBLEM-SEARCH TRAINING AS EFFECTIVE MEANS OF THE MIND STUDENT DEVELOPMENT (Pedagogy of Higher and Secondary Education, 2022)
The right organization of the problematic-searching education and its effectiveness in the development of the mental forces and abilities of the students is considered in this article.